What does poverty feel like? Urban inequality and the politics of sensation. (April 2020) - Jaffe, Rivke; Dürr, Eveline; Jones, Gareth A; Angelini, Alessandro; Osbourne, Alana; Vodopivec, Barbara
The emergent field of 'sensory urbanism' studies how socio-spatial boundaries are policed through sensorial means. Such studies have tended to focus on either formal policies that seek to control territories and populations through a governance of the senses, or on more everyday micro-politics of exclusion where conflicts are articulated in a sensory form. This article seeks to extend this work by concentrating on contexts where people deliberately seek out sensory experiences that disturb their own physical sense of comfort and belonging. While engagement across lines of sensorial difference may often be antagonistic, we argue for a more nuanced exploration of sense disruption that attends to the complex political potential of sensory urbanism. Specifically, we focus on the politics of sensation in tours of low-income urban areas. Tourists enter these areas to immerse themselves in a different environment, to be moved by urban deprivation and to feel its affective force. What embodied experiences do tourists and residents associate with urban poverty? How do guides mobilise these sensations in tourism encounters, and what is their potential to disrupt established hierarchies of socio-spatial value? Drawing on a collaborative research project in Kingston, Mexico City, New Orleans and Rio de Janeiro, the article explores how tours offer tourists a sense of what poverty feels like. Experiencing these neighbourhoods in an intimate, embodied fashion often allows tourists to feel empathy and solidarity, yet these feelings are balanced by a sense of discomfort and distance, reminding tourists in a visceral way that they do not belong.